critical study of initial pushto resistance literature, before Ghani Khan - Irfanullah; Dr. Yasmeen Sultana (Zaban-o-Adab, 2021)
The Pashto language is the oldest language, as per critics, it is thousands of years old. Like other great literature, Pashto also starts its poetic Journey from their basic folk traditional common poetry like “Tapa” (two-line stanza). Pashto “Tapa” represents the history of Pashto language as well as Pashto resistance and revolutionary poetry. As we know poetry represents the circumstances and surroundings of a particular era, the History of Pushtoon shows that they had always been in war against the invaders, therefore profound portion of Pashto poetry expresses the element of resistance against such condition, that’s why initial poets of Pashto poetry contain these war elements and endurance in their poetry like Ameer Karoor, Malik Yar Georges, Baba Hootak and Khush Hal Khan Khatak. Even though, Rehman Baba who is recognized as a spiritual (Sofia) poet had this element of resistance and revolution in his poetry. For example, he says under a cruel ruler there is no difference in Peshawar, grave and home. After this Abdul Hameed Mashokhail, Kazim Khan Shaida, Ahmed Shah Abdali and Noor Deen are also acknowledged for their resistance and revolutionary poetry.